2023
DOI: 10.3390/su15107972
|View full text |Cite
|
Sign up to set email alerts
|

Trends and Challenges of Technology-Enhanced Learning in Geotechnical Engineering Education

Abstract: The integration of technology and new tools in engineering education has created opportunities for the advancement of geotechnical engineering education (GEE). Technology-enhanced learning (TEL) has been implemented in GEE by many educators, and its impacts have been studied by different researchers. This review paper presents a comprehensive analysis of the state-of-the-art implementation of TEL in GEE based on published journal articles. This study adopts a systematic approach in examining the literature on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…Also, the quantitative and qualitative analysis revealed that the introduction of ICT-supported, electronic, virtual, and blended learning environments positively affects military engineering education and increases training effectiveness, cadets' performance, and resource utilization. The research supported the previous findings, showing that technology-enhanced learning creates opportunities for the improvement of the educational process and the development of learners' practical skills (Rehman, 2023). It was found that positive technology-enhanced learning provides cadets with flexibility and makes learning more personalized (Ivanović et al, 2018).…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…Also, the quantitative and qualitative analysis revealed that the introduction of ICT-supported, electronic, virtual, and blended learning environments positively affects military engineering education and increases training effectiveness, cadets' performance, and resource utilization. The research supported the previous findings, showing that technology-enhanced learning creates opportunities for the improvement of the educational process and the development of learners' practical skills (Rehman, 2023). It was found that positive technology-enhanced learning provides cadets with flexibility and makes learning more personalized (Ivanović et al, 2018).…”
Section: Discussionsupporting
confidence: 86%
“…In the context of engineering education, technology-enhanced learning has opened up opportunities for the advancement of the educational process, enabling learners to engage with complex practical experiences in innovative ways (Rehman, 2023). Efficient technologyenhanced learning has demonstrated its capacity to improve training in technical competence, personal development, and contextual intelligence (Licciardello et al, 2021).…”
Section: Creation and Development Of Technology-enhanced Learningmentioning
confidence: 99%
See 2 more Smart Citations
“…The integration of new technologies in education, including sensors, and the fast evolving way in which we generate, process, and revise information are bound to have a major impact on how we teach and learn [8]. Technology-enhanced learning has revolutionized traditional educational practices by leveraging innovative tools and applications to enhance teaching and learning experiences [9,10]. AR and VR simulations transport students to immersive virtual environments, while mobile devices equipped with various sensors (e.g., gyroscopes, accelerometers) allow for personalized learning experiences, adapting to individual preferences and movements.…”
Section: Introductionmentioning
confidence: 99%